Respuesta :

Answer:

B

Step-by-step explanation:

Substitute x = 5 into the expression

[tex]\frac{4(5+5)(5+1)}{(5+3)(5-3)}[/tex]

= [tex]\frac{4(10)(6)}{8(2)}[/tex]

= [tex]\frac{240}{16}[/tex]

= 15 → B

Answer:

15

Step-by-step explanation:

Numerator ; 4(X+5)(X+1)

substitute : X=5

The first expression becomes : 4(5+5)(5+1)

= 4(10)(6)

=4×10×6

=240

Denominator : (X+3)(x-3)

substitute: X=5

=(5+3)(5-3)

=(8)(2)

=16

Now, Dividing the numerator by the denominator we have 240÷16=15

ACCESS MORE